Personal and technological skills to coach people with noncommunicable diseases: development and validation of a scale for nursing students. - Ferreira, Paulo Alexandre Carvalho (2021)
Background:Current international policies converge to the need of empowering patients and families in becomingmore autonomous in the self-caring and management of their noncommunicable diseases (NCDs). Given theirprofessional scope, nurses are the most well-positioned health professionals to answer this societal challenge. Inthe literature, health coaching and the use of information and communication technologies (ICTs) emerge as twostill under-used contributions to nursing practice in this regard. Given the lack of instruments and researchdeveloped so far in the use of health coaching and ICTs during nurses training, we aim to develop a scale thatexplores nursing students'perceptions regarding their coaching skills of people with NCDs and the potential roleof ICTs in this domain.Methods:After a comprehensive literature review, an initial items list (n¼39) was delineated and discussed by apanel of international experts. After conceptual and structural consensus, the pre-validated version of the Personaland Technological Skills to coach people with noncommunicable diseases scale (PTSC-NCD scale) was created.Then, the pre-validated PTSC-NCD scale was translated to Portuguese, Finnish, Flemish and Slovenian followingBeaton and colleagues'recommendations, and applied to undergraduate nursing students infive European uni-versities. Principal component analysis and reliability analysis were performed in each country through thestatistical program Statistical Package for the Social Sciences (version 22.0). All ethical assumptions were com-plied with throughout this study.Results:874 nursing students enrolled in the study, predominantly female (71.1%) and with a mean age of 22.4years (SD¼5.49). After data analysis across international settings, three dimensions emerged: Coaching CentredPersonal Skills (F1); Digital Technology Improving Patient-Centred Care (F2); and Digital Technology ImprovingRelational Skills (F3). All the dimensions showed good reliability (Cronbach's alpha>.80).Conclusion:The PTSC-NCD scale evidence good validity and reliability indicators across different internationalsettings.